Study of Esterification Reaction Between Ethanol and Acetic Acid Using Homogeneous and Heterogeneous Catalyst - Nuryoto, Nuryoto; Amaliah, Alin Rizka; Puspitasari, Anita; Ramadhan, Anggara Diaz (World Chemical Engineering Journal, 2020)
The Ethyl acetate is the final product of esterification reaction between ethanol and acetate acid which usually used as a solvent. Catalysts are used to boost the esterification reaction rate, mostly the homogenous catalyst (acid liquid catalyst) is used. The use of homogeneous catalyst needs quite long process to separate, that is the reason why using the heterogeneous catalyst is the alternate way. The purpose of this research is to compare the performance of homogeneous catalyst (sulphuric acid) and heteregenous catalyst (natural zeolite from Bayah) by variating the factors that has an impact on reaction. The reaction was happened in batch reactor by variating the speed of agitation speed in range 500-700 rpm and the catalyst molecules size 60 mesh and 100 mesh for the solid catalysts. The goal of the variation is to maximize the reactant mass transfer to the active site of the catalyst. The result of this research shows that on the agitation speed of 700 rpm and 100 mesh Bayah natural zeolite is able to yield bigger conversion of acetate acid compared to using the sulphuric acid catalyst, which are 45.03% and 15.19% .